Potensi Antimikroba Ekstrak Infus Daun Pedada (Sonneratia caseolaris L) Mandeh, Sumatera Barat - Jannah, Mifthahul; Nurlaili , Nurlaili; Harsachatri , Deasy Ovi; Novia, Novia; Larasati , Julia Veronika; Arfan , Alya Rahmaditya; Pangestika , Yuliandini; Habibi , Alif Rahman; Agustien , Anthoni (Journal of Pharmaceutical and Sciences, 2026)
The increasing emergence of antibiotic-resistant bacteria poses a serious global health threat, highlighting the need for alternative antimicrobial sources derived from natural products. Pedada mangrove (Sonneratia caseolaris L.), widely distributed in the coastal area of Mandeh, West Sumatra, has been traditionally used as a medicinal plant. This study aimed to evaluate the antimicrobial potential of leaf infusion extracts of Sonneratia caseolaris and to determine the effect of heating time variation on antimicrobial activity. Leaf infusion extracts were prepared using boiling water with heating durations of 10, 15, and 30 minutes. Antimicrobial activity was assessed against Escherichia coli, Staphylococcus aureus, and Candida albicans using the disc diffusion method. The results showed that all infusion extracts exhibited antimicrobial activity with varying inhibition levels. The optimal heating time was 10 minutes, resulting in inhibition zone diameters of 10.5 mm against E. coli, 10 mm against S. aureus, and 10 mm against C. albicans. These findings indicate that Sonneratia caseolaris leaf infusion extract has potential as a natural antimicrobial agent, with shorter heating time being more effective in preserving antimicrobial activity.